The analysis of sediment mobility in the Kemaman River Estuary, Terengganu: A preliminary investigation / Mohd Ekhwan Toriman - Toriman, Mohd Ekhwan (2004)
Over the past 10 years, Kemaman River estuary demonstrates severe coastal erosion due to natural and man-made activities. It is estimated that approximately 44, 000 m3 sediments (sand beach) were eroded along the coastal with maximum destruction occurred during the monsoon season. Following the problem, this study was engaged in order to investigate the mobility, transfer and deposition of sediment within the river estuary. In this research, the artificial radionuclide of Caesium 137 (137Cs) was used as a tracer to investigate sediment characteristics from a period of november 2003-Febmary 2004. The results provide useful information of the potential to document both rates and patterns of sediment mobility within the Kemaman River estuary. Spatial analysis on sediment properties indicated that the beach consisting highly sand and silts (78.45 percent) compared with coarse (23.15 percent) for backshore and foreshore zones. Meanwhile, the temporal distribution indicates that sediment mobility were active during the monsoon season. The sediment fingerprints traveled as far as 6.4 km towards south of Pantai Chendor causing imbalance on sediment budget along the river estuary. As a result about 2 km of Kemaman River estuary was subjected to severe coastal erosion during the study period. Using the equilibrium beach profile concept, the model outputs the volume of sand required to re-create a beach fill of the specified width. By given a specific native and fill grain sizes, fill width, berm high and depth of closure, the model estimated of 16, 870 m) volume sand required per 70 m beach width. As the sediment mobility and problem related to coastal erosion demonstrate more active in the future, this study suggests both long and short term actions to minimize the problem.